Challenges for Adolescent's Sexual and Reproductive Health within the Context of Universal Health Coverage - Cortez, Rafael (World Bank, Washington, DC, 2018)
Young people (10-24 years of age), around the world face tremendous challenges to meeting their sexual and reproductive health (SRH) needs. Inadequate access to health information and services, as well as inequitable gender norms, contributes to a lack of knowledge and awareness about puberty, sexuality, and basic human rights. This can have serious implications on young people s health and welfare as well economic development and poverty reduction. Given the importance of ASRH within the context of development as well as the paucity of data on the issue, the WBG conducted a global analysis and country case studies in order to: (i) gain a deeper understanding of the multi-sectoral determinants of ASRH outcomes; (ii) explore further the multi-sectoral supply and demand-side determinants of access, utilization, and provision of services relevant to identified ASRH outcomes; and (iii) identify multi-sectoral programmatic and policy options to address critical constraints to improving ASRH outcomes that can inform WBG lending operations and policy dialogue.